2014
DOI: 10.3945/ajcn.113.079392
|View full text |Cite
|
Sign up to set email alerts
|

Human protein status modulates brain reward responses to food cues

Abstract: Protein status modulates brain responses in reward regions to savory food cues. These novel findings suggest that dietary protein status affects taste category preferences, which could play an important role in the regulation of protein intake in humans. This trial was registered at www.trialregister.nl/trialreg/admin/rctview.asp?TC=3288 as NTR3288.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 36 publications
4
59
1
2
Order By: Relevance
“…Other studies have attempted to examine underlying mechanisms for this phenomenon. Some insight might come from recent papers examining the brain's response to savory food cues (Griffioen-Roose et al, 2014). When adults were in a low-protein dietary state, brain response in the inferior orbitofrontal cortex (implicated in emotion and reward-driven decision-making) was higher for savory food odor and visual cues relative to a control condition, and the participants also exhibited a higher preference for savory foods (Griffioen-Roose et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have attempted to examine underlying mechanisms for this phenomenon. Some insight might come from recent papers examining the brain's response to savory food cues (Griffioen-Roose et al, 2014). When adults were in a low-protein dietary state, brain response in the inferior orbitofrontal cortex (implicated in emotion and reward-driven decision-making) was higher for savory food odor and visual cues relative to a control condition, and the participants also exhibited a higher preference for savory foods (Griffioen-Roose et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Some insight might come from recent papers examining the brain's response to savory food cues (Griffioen-Roose et al, 2014). When adults were in a low-protein dietary state, brain response in the inferior orbitofrontal cortex (implicated in emotion and reward-driven decision-making) was higher for savory food odor and visual cues relative to a control condition, and the participants also exhibited a higher preference for savory foods (Griffioen-Roose et al, 2014). Additionally, another study found a relationship between a polymorphism in the FTO gene, which has been associated with body mass index and obesity risk, and greater total energy and protein intake, but lower carbohydrate intake (Qi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a 14-d low-protein diet (0·5 g protein/kg body weight·per d) was found to increase protein intake, wanting, preference for savoury high-protein foods (22) and the neural activation to savoury food cues in brain reward regions (23) compared with a high-protein diet (2·0 g protein/kg body weight per·d). Although these data suggest that dietary macronutrients may also differentially affect food hedonics, the acute effects of macronutrient composition, and in particular dietary fat, on food hedonics has yet to be examined.…”
mentioning
confidence: 93%
“…A corollary to this hypothesis is that a reduction in the dietary protein concentration would increase total energy intake, due to overconsumption of carbohydrates and fat, in an effort to meet protein requirements. Consistent with this, moderately protein deficient diets were found to produce hyperphagia in rodents [6][7][8][9] and in some 1,10,11 but not all human studies 12,13 , whereas, severe protein restriction below a certain threshold leads to a reduction in food intake in rodents 9,14 . However, little is known of the underlying mechanisms by which moderate protein deficiency elicits such behavioural and metabolic adaptations and promotes positive energy balance with consequent predisposition to obesity and other metabolic disorders.…”
mentioning
confidence: 67%
“…Although the low protein-induced hyperphagia is associated with a central orexigenic drive 11,[15][16][17][18] , the peripheral signals that transmit information to central neural networks are poorly defined. To discern potential peripheral mediators, we focussed on circulating concentrations of amino acids, anorexigenic gut hormones, and peripheral serotonergic 5HT3, β -adrenergic and FGF21 signaling.…”
Section: Discussionmentioning
confidence: 99%